1986
DOI: 10.1111/j.1467-6494.1986.tb00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Logical learning theory: A teleological alternative in the field of personality

Abstract: Logical leanung theory (LLT) is presented as a teleological alternative to most current explanations of human behavior An organism construed as intentional IS more suitable to many personality/personological accounts than is an organism construed as mechanical It is first established that LLT is a predicational rather than a mediational explanation of behavior Tlie concept oStelosponstvity is then presented as an altemabve to the predominant view of hehavior as a supposed response to antecedent sbmulation Telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The contradictory nature of many psychological perspectives has been well documented (e.g., Danziger, 1990; Furedy & Furedy, 1982; Kimble, 1984; Koch, 1976; Rychlak, 1981, pp. 519–538; 1984; Slife & Williams, 1995, pp. 46–48; Wertheimer, 1988; Yanchar, in press).…”
Section: Critique Of Integrationismmentioning
confidence: 99%
See 1 more Smart Citation
“…The contradictory nature of many psychological perspectives has been well documented (e.g., Danziger, 1990; Furedy & Furedy, 1982; Kimble, 1984; Koch, 1976; Rychlak, 1981, pp. 519–538; 1984; Slife & Williams, 1995, pp. 46–48; Wertheimer, 1988; Yanchar, in press).…”
Section: Critique Of Integrationismmentioning
confidence: 99%
“…An examination of Dollard and Miller's work reveals that rather than integrate these two competing theories, these researchers altered the theoretical nature of psychoanalysis so that it fit the behavioristic framework they advocated. Rychlak (1981Rychlak ( , 1984, for one, has argued that Dollard and Miller's work removed essential aspects of Freudian theory, such as self-direction, and in so doing dealt with a theory that was not recognizably Freudian. In this sense, Dollard and Miller did not integrate behaviorism and psychoanalysis because they never treated psychoanalysis as psychoanalysis.…”
Section: Critique Of Integrationismmentioning
confidence: 99%
“…The theory of reality, consisting of a world theory, a self-theory, and connecting propositions, is built from implicit beliefs and is developed to make life as emotionally satisfying as possible. Hogan (1987) has suggested that personality can be defined in two distinct ways deriving from two different spheres of experience: that of the observer and that of the actor (see also Rychlak, 1986). According to Hogan, the trait approach to personality provides psychologists with a sophisticated set of criteria for describing personality from the perspective of the observer, that is, for describing a person's distinctive social stimulus value.…”
Section: Author and Constmct Definitionmentioning
confidence: 99%
“…Much work has been done already. Joseph Rychlak’s (1979, 1988, and in press) work on agency is among the most thorough and careful in the history of the discipline. The strength of his position is that it refuses to compromise with traditional determinism.…”
Section: Two Discourses About Agencymentioning
confidence: 99%